2013
DOI: 10.1055/s-0033-1350693
|View full text |Cite
|
Sign up to set email alerts
|

Gewachsene Erfordernisse im anspruchsvollen viszeralchirurgischen Management bei morbider Adipositas - Was muss der Viszeralchirurg wissen?

Abstract: In the international comparison and in Europe, the Federal Republic of Germany belongs to the countries with a very high prevalence of obesity (men, 67.1 %; women, 53 %). Among the European countries, the incidence of diabetes mellitus type 2 is also high ("Study of the health of adults in Germany" [DEGS]) - Robert Koch Institute). Not only for surgeons, this can be considered as a great challenge even in usual abdominosurgical interventions. 1. Surgical equipment needs to be adapted to the requirements for ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Not only bariatric surgeons but also all other physicians involved in the medical aftercare of such patients should be aware of the risks of vitamin, trace element and electrolyte deficiencies after bariatric surgery and how these deficiencies can be diagnosed and treated [ 9 , 10 ]. In case of clinical suspicion or deferred parenteral nutrition, the immediate introduction of a thiamine substitution is necessary to minimize the risk of catastrophic consequences.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only bariatric surgeons but also all other physicians involved in the medical aftercare of such patients should be aware of the risks of vitamin, trace element and electrolyte deficiencies after bariatric surgery and how these deficiencies can be diagnosed and treated [ 9 , 10 ]. In case of clinical suspicion or deferred parenteral nutrition, the immediate introduction of a thiamine substitution is necessary to minimize the risk of catastrophic consequences.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found a beriberi incidence prior to bariatric surgery procedures of approximately 15.5% [ 12 , 13 , 14 ]. In women, the thiamine level is lower than in men [ 9 ]. A retrospective analysis from the literature indicated that 29% of patients suffer from thiamine deficiency prior to bariatric surgery [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caucasians usually show a smaller incidence of low serum thiamine levels. In women, serum thiamine levels are lower than in men [25]. It has been reported that 5-30 % of patients undergoing bariatric surgery suffered from subnormal serum thiamine levels prior to the treatment [26,27].…”
Section: Risk Factorsmentioning
confidence: 99%